Peningkatan Kualitas Layanan Satu Pintu di Kota Semarang dengan Penerapan Hard Skill dan Soft Skill - Widiastuti, Tantri; Aditya, Elma Muncar; Paranita, Ekayana Sangkasari (Jurnal Aplikasi Manajemen, 2015)
Service one door or one stop service (OSS) is a step that can be applied in variousareas in order to increase investment and the one-stop service is expected in reducing thebureaucrat, therefore the process of licensing become shorter. In general, this study aims toimprove the satisfaction of investors who are conducting the licensing process in Semarang.There are 50 employees who are likely to occupy the part of the ministry, therefore thenumber of employees who take the test reach 50 employees who have been appointed by thehead of the Badan Pelayanan Perijinan Terpadu (BPPT). The data analysis uses IPA (Importanceand Performance Analysis). The results showed that (1) employees'IQ in terms of hardskills at Badan Pelayanan Perijinan Terpadu (BPPT) Semarang are in the level of average.The test that has taken showed less score in terms of the pace of work, precise work, jobstability and work endurance. As for soft skills, which are still getting less score is communication,self-confidence, self-control and emotional stability, showing that only 14 employeeswho meet the qualifications for employment services (front desk) that directly deal with therespondent (front desk). (2) Analysis of the level of satisfaction of respondents indicated thatthe services provided to the respondents do not meet the wishes of the respondents as theaverage value of the performance was lower than expectations of respondents. (3) Takinginto account the hard skills and soft skills of employees in the public service model thatsatisfy investors, the satisfaction of investors who are conducting the licensing process canbe increased.